PENGARUH KOMPENSASI, PENDIDIKAN DAN PELATIHAN, PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL KUTA PARADISO KUTA, BADUNG - Kesuma, I Gst. Ngr. Ag. Indra; Riana, Gede (E-Jurnal Manajemen, 2015)
The company's goal is achieved if optimum employee performance, so it is important in the organization's efforts to achieve its objectives, so it is important to note the variables that determine the performance of employees. Kuta Paradiso Hotel Kuta, Badung paying attention and the problems encountered with regard to compensation, education and training, occupational safety and health programs to improve employee performance. The study was conducted in order to know the effect of compensation, education and training, occupational health and safety programs on employee performance. Stratified random sampling method is used to determine the sample, as many as 76 employees. Data were collected by interview and questionnaire. Analysis of data using multiple linear regression analysis techniques, the F-test, hypothesis testing (t-test) and the standardized beta coefficients. Based on the results of the discussion, the conclusion obtained results that kmpensasi research, education and training, occupational health and safety programs partially positive and significant effect on the performance of employees at Kuta Paradiso Hotel Kuta, Badung. The results showed increased compensation will increase employee performance, the better the education and training it will improve the performance of employees, and the increasing performance of employees is determined by improvements in the implementation of occupational safety and health programs.
Keywords: compensation; training; K3; performance.